Schaarste is goed, maar de selectie moet beter - Seuren, L (Amsterdam University Press, 2016)
Hornikx and Batenburg (2016) demonstrate that publication pressure is an important reason why the social sciences face a problem with replicability. They argue that researchers result to questionable methods because the opportunities to publish are scarce. This paper, however, suggests that more room for publications will not lead to better research practices. Instead the scientific community should focus on stimulating good methods: (i) use power analyses to make sure an experiment is adequately sensitive and (ii) value the effect size over statistical significance.